Bilateral relations between Belarus and the United States of America: a history of hopes and disappointments - Snapkouski, Uladzimir E. (Journal of the Belarusian State University. International Relations, 2022)
The history of the bilateral relations between Belarus and the United States from 1991 to 2020 was difficult and controversial. In 1991–1996 the relationship was positive and dynamic, extending to many areas from international security to humanitarian contacts and exchanges among people. After the 1996 referendum, the relationship soured. Washington adopted a policy of selective engagement, with limited dialogue with the government and more extensive support for humanitarian contacts, civil society and trade links. From 2013 to June 2020 Minsk and Washington took tentative steps towards normalcy, but in 2020 the dynamic reversed again.
Keywords: Republic of Belarus; United States of America; bilateral relations; diplomatic relations; economic ties; foreign policy; policy of selective engagement